Sloshing behaviours of rectangular and cylindrical liquid tanks subjected to harmonic and seismic excitations. - Chen, Yung-Hsiang
A numerical and experimental study on the sloshing behaviours of cylindrical and rectangular liquid tanks is addressed. A three-dimensional boundary element method for space with the second-order Taylor series expansion in time is established to simulate the sloshing phenomenon and its related physical quantities inside a liquid tank subjected to horizontal harmonic oscillations or recorded earthquake excitations. The small-scale model experiments are carried out to verify some results of numerical methods in this study. The comparisons between numerical and experimental results show that the numerical method is reliable for both kinds of ground excitations. Finally, the water wave and the base shear force of a rectangular tank due to harmonic excitation are also presented at different frequencies. A huge cylindrical water tank subjected to a recorded earthquake excitation is used for application and discussion.
Keywords: Nonlinear sloshing; BEM; Seismic excitation